2016
DOI: 10.1111/jphp.12588
|View full text |Cite
|
Sign up to set email alerts
|

Fingolimod hydrochloride gel shows promising therapeutic effects in a mouse model of atopic dermatitis

Abstract: This study shows that the gels containing 0.50% FNGL and FNGL 0.50% plus 6% colloidal oatmeal have potential for the treatment of AD. The presence of colloidal oatmeal may provide additional benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Furthermore, FTY720 inhibited the migration of dendritic cells from the skin to the lymph nodes [ 82 ]. In addition to these reports, it has also been shown that FTY720-containing gel decreases the Eczema Area and Severity Index (EASI) score of AD-like lesions in SKH-1 hairless mice [ 83 ]. FTY720 is also effective in psoriasis.…”
Section: S1p and S1pr Modulators For Skin Diseasesmentioning
confidence: 99%
“…Furthermore, FTY720 inhibited the migration of dendritic cells from the skin to the lymph nodes [ 82 ]. In addition to these reports, it has also been shown that FTY720-containing gel decreases the Eczema Area and Severity Index (EASI) score of AD-like lesions in SKH-1 hairless mice [ 83 ]. FTY720 is also effective in psoriasis.…”
Section: S1p and S1pr Modulators For Skin Diseasesmentioning
confidence: 99%